The verifiable secure schemes for resisting attacks in cloud deduplication services. (2016) - Li, Xuan; Shen, Yongluo; Zhang, Jun
Data deduplication is an impactful technology in cloud storage services which permits the cloud side to save the storage space by eliminating the duplicated data. In this paper, we study the risk of deduplication in cloud storage services. Two typical security issues on how clients can be cheated are demonstrated and analysed. Those attacks may result in data losses to the clients. We therefore propose two mechanisms that make the verification of data deduplication feasible. The proposed verification models can effectively reduce the risk of data deduplication.